Léxico estratigráfico del Perú - Teves Rivas, Nestor (2001)
Colaboradores técnicos: Carmen San Román, Fernando Rebaza Grados, Manuel Acaro Chuquicaña, Javier Espinoza Rodriguez, Percy Mosqueira Vasquez